THE IMPACT OF VITAMIN D3 LEVELS ON RECOVERY AND REHABILITATION FOLLOWING SURGICAL TREATMENT OF FEMORAL NECK FRACTURES: A NARRATIVE REVIEW - Piotr Komasara; Tomasz Szwarc; Mateusz Kałwik; Paweł Mikołajczak; Julia Nowakowska; Piotr Modzelewski; Irmina Czerepak; Milena Krawczyk; Bartłomiej Sałapski; Karolina Niewczas (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Femoral neck fractures are a major source of morbidity and mortality among older adults, frequently leading to prolonged hospitalization, disability, and loss of independence. Vitamin D3 plays a central role in bone metabolism, muscle function, and immune modulation- all crucial for postoperative recovery. However, the clinical relevance of vitamin D3 status in patients undergoing surgery for femoral neck fractures remains incompletely understood. This narrative review aims to synthesize current evidence on the relationship between vitamin D3 levels and key outcomes including functional recovery, complication rates, and mortality in this population.Material and method: A comprehensive literature search was conducted in PubMed and Embase using Boolean operators and relevant medical subject terms. Filters limited the search to full-text, English-language studies published between 2020 and 2025 involving human subjects. In Embase, only randomized controlled trials and systematic reviews were included. A total of 98 non-duplicate studies were screened; 34 were selected for full-text analysis and thematic synthesis.Results: Most studies demonstrate a positive association between sufficient 25(OH)D levels and faster mobility recovery, improved functional scores (e.g., Harris Hip Score, Barthel Index), and better postoperative quality of life. Vitamin D3 deficiency is consistently linked to higher rates of infectious complications, delayed fracture healing, and increased fall risk. Several studies also associate low 25(OH)D levels with elevated short-term mortality. Supplementation strategies appear beneficial, although optimal dosing and timing remain under debate.Conclusions: Vitamin D3 status is a potentially modifiable factor influencing outcomes after femoral neck fracture surgery. Routine screening and appropriate supplementation should be considered as part of multidisciplinary perioperative care. Further randomized trials are needed to define causal relationships and refine clinical protocols.